Manajemen Risiko Terhadap Praktik Akad Hybrid Pada Pembiayaan UMKM di Indonesia Melalui Digitalisasi Perbankan Syariah - Wahyudi, Ilham (Moderasi : Journal of Islamic Studies, 2025)
This study aims to evaluate the effectiveness of implementing hybrid contract-based financing models in supporting the financing of Micro, Small, and Medium Enterprises (MSMEs) by Islamic banking institutions in Indonesia, particularly in the context of ongoing digital transformation. The hybrid contract (akad hybrid) is an innovation that integrates two or more Sharia-compliant contracts into a single financing product, offering flexibility and tailored solutions to meet the complex financial needs of MSMEs. While the model provides several advantages, it also presents significant challenges, especially in terms of compliance with Sharia principles and the management of increasingly complex operational risks in the digital era. This research adopts a qualitative approach using a case study method involving three major Islamic banks in Indonesia: Bank Syariah Indonesia, Bank Muamalat, and Bank Mega Syariah. Data were collected through in-depth interviews with internal bank personnel, such as financing managers and risk analysts, as well as MSME clients. Document analysis of relevant bank policies was also conducted. The findings indicate that hybrid contracts have been effective in expanding MSME financing access, particularly in the trade and service sectors. However, notable risks persist, including inconsistency in contract implementation with Sharia regulations, limited customer understanding of contract structures, and technical challenges in digital-based monitoring. Therefore, the study recommends that Islamic banks enhance their technology-based risk management systems and expand digital Sharia contract education for MSME actors. These findings contribute significantly to the development of innovative and sustainable Sharia financing products that align with the dynamics of the digital economy.